ANALISIS KONSEP PRODUK, PASAR SASARAN, DAN STRATEGI PEMASARAN USAHA MINUMAN TEH MODERN JOY TEA BERBASIS PENDEKATAN 4P - M. Afrizal Miradji; Abdul Rozaq; Anggun Nabillah Putri Umam; Ariya Dwi Eriyanto; Ribka Cahyani lestari Zebua (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Joy Tea is a modern drink business that focuses on tea, created to meet the needs of the public for refreshing, high-quality, and affordable drinks. The products offer a variety of flavors, ranging from pure tea to fruit and milk blends, making them enjoyable for different groups, especially students, college students, and young workers. The purpose of this research or report is to analyze the product concept, target market, marketing strategies, and potential for business development of Joy Tea. The approach used includes direct observation, market analysis, and the 4P marketing method (Product, Price, Place, Promotion). The analysis results show that Joy Tea has a significant opportunity for growth due to consumer interest in modern tea drinks, competitive pricing, and regular updates to its flavor offerings. With the right marketing strategies, Joy Tea can become a popular and competitive brand in the current beverage market